Pengaruh Kemasan Jajanan Floaty Snack dengan Ilustrasi Hewan terhadap Persepsi Konsumen - Praditya, Angga; Isnaini, Wiwi (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2025)
Packaging design plays an important role for consumers in making purchasing decisions, one of the first assessments of consumers of products is clear product attributes and attractive visual appearance. An attractive design can evoke and increase product visibility. However, visuals can also affect the initial perception of a product, which can be positive or negative. The case study of a snack packaging called Floaty Snack uses illustrations mainly a picture of a cat, which resulted in a fairly high purchase interest but also resulted in misunderstanding and perceived as cat food. This research is a mixture of qualitative and quantitative methods, conducted through interviews and questionnaires. The results of this study are expected to provide insight into the impact of using animal illustrations on perceptions and flavors built among consumers.